Integrating Maternal Health Literacy and the Health Belief Model for Predicting Preeclampsia Screening Adherence - Sonia Novita Sari; Sri Murtini; Yesica Geovany Sianipar; Nova Isabella Mariance Br Napitupulu; Amelia Erawaty Siregar; Natalya Rut Naomi Nainggolan (Asosiasi Dosen Muda Indonesia, 2026)
Preeclampsia remains one of the leading causes of maternal morbidity and mortality, highlighting the importance of improving pregnant women's adherence to early screening and timely clinical decision-making. Objective: This study aims to examine the integrated role of Maternal Health Literacy (MHL) and the Health Belief Model (HBM) in predicting preeclampsia screening adherence and mitigating delays in medical decision-making among pregnant women. Methods: A quantitative predictive study with a cross-sectional design was conducted involving 64 pregnant women at the Sarfina Sembiring Primary Clinic selected through purposive sampling. Data were collected using validated questionnaires measuring MHL and HBM constructs and analyzed using multiple logistic regression. Findings: The results showed that both MHL and HBM significantly predicted preeclampsia screening adherence and mitigation of delay in decision-making. HBM was identified as the strongest predictor of screening adherence (OR = 6.52), whereas MHL demonstrated the greatest influence on reducing delays in clinical decision-making (OR = 8.21). These findings indicate that psychological beliefs and cognitive health literacy play complementary roles in improving maternal preventive health behavior. Implications: The findings support the development of integrated maternal health education programs that combine health literacy enhancement with behavior-based interventions, including digital health education and counseling, to strengthen screening adherence and maternal self-efficacy in primary healthcare settings. Originality: This study proposes and empirically validates an integrated predictive framework combining Maternal Health Literacy and the Health Belief Model. Unlike previous studies that examined these constructs separately, this research demonstrates their complementary roles in improving preeclampsia prevention strategies and reducing delays in maternal healthcare decision-making.